Distribution of synchrotron relativistic plasma emission over quasar radio lobes - Kontorovich, V.M.; Kolesnikov, F.M. (Вопросы атомной науки и техники, 2001)
Asymmetrical lobe structures of radio galaxies and quasars can be explained in the diffusion model with the moving hot spot (the source of ultra relativistic electron plasma) by the possible jet precession. The equation for the space-time nonuniform electron distribution function, describing the synchrotron losses and the diffusion of electrons from the hot spot into the lobes, is solved analytically. The space distributions of the synchrotron emission intensity and the spectral indices on the lobe are calculated numerically for different parameters of the jet precession and the diffusion.